2011
DOI: 10.3390/polym3020762
|View full text |Cite
|
Sign up to set email alerts
|

Polyelectrolyte Complex Nanoparticles of Poly(ethyleneimine) and Poly(acrylic acid): Preparation and Applications

Abstract: Abstract:In this contribution we outline polyelectrolyte (PEL) complex (PEC) nanoparticles, prepared by mixing solutions of the low cost PEL components poly(ethyleneimine) (PEI) and poly(acrylic acid) (PAC). It was found, that the size and internal structure of PEI/PAC particles can be regulated by process, media and structural parameters. Especially, mixing order, mixing ratio, PEL concentration, pH and molecular weight, were found to be sensible parameters to regulate the size (diameter) of spherical PEI/PAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 31 publications
0
37
0
Order By: Relevance
“…At low ionic strength, the main driving force of the complexation process is the gain in entropy, caused by the release of the low-molecular weight counterions, initially bound to the polyelectrolyte backbone. Hydrogen bonding or Van der Waals interactions are other types of interactions which can also contribute to the ion-pairing process [2][3][4]. Apart from nanoparticles with a densely charged, yet net neutral surface, an uncharged nanoparticle may be also considered as mucoinert as viral capsids, provided it is sufficiently hydrophilic with a low hydrogen bonding http capability (e.g., polyethylene glycol (PEG), cyclodextrin coatings) [1,5].…”
Section: Introductionmentioning
confidence: 99%
“…At low ionic strength, the main driving force of the complexation process is the gain in entropy, caused by the release of the low-molecular weight counterions, initially bound to the polyelectrolyte backbone. Hydrogen bonding or Van der Waals interactions are other types of interactions which can also contribute to the ion-pairing process [2][3][4]. Apart from nanoparticles with a densely charged, yet net neutral surface, an uncharged nanoparticle may be also considered as mucoinert as viral capsids, provided it is sufficiently hydrophilic with a low hydrogen bonding http capability (e.g., polyethylene glycol (PEG), cyclodextrin coatings) [1,5].…”
Section: Introductionmentioning
confidence: 99%
“…dextran-sulphate) together with the organic polycation cross-linker PEI can form a nanoparticle polyelectrolyte complex by self-assembly through electrostatic intermolecular interactions (Müller et al 2011). In time, the PEC particle will unfold, releasing the cross-linker.…”
Section: Bulk Experimentsmentioning
confidence: 99%
“…In order to extend the gelation time it is desired to make a cross-linker, which is a polycation, less active by mixing it with a retardant, polyanion. As a result of that reaction, a polyelectrolyte complex (PEC) is formed (Cordova et al 2008;Müller et al 2011;Spruijt 2012;Jayakumar and Lane 2012). Over time the chemical bonds between the polycation and the polyanion become weaker and the cross-linker becomes available for interaction with HPAM.…”
Section: Introductionmentioning
confidence: 99%
“…25,26 This property may be applied for the immobilization of proteins and enzymes, [27][28][29] anchoring metal nanoparticles, 30 or drug delivery. 31,32 Different authors have reported ionomer complex micelles of PEI grafted with methoxypolyethylene glycol (mPEG) and anionic surfactants, 9,33 metal ions (AuCl 3 or PtCl 6 2-), 26,34 oligonucleotides, 35 or plasmid DNA. 36 The covalent attachment of mPEG is commonly used to improve aqueous solubility and to reduce immunogenicity and cytotoxicity of polymeric systems.…”
Section: +mentioning
confidence: 99%